The influence of firm age and firm size on strategic agility and firm performance moderated by environmental uncertainty in creative industry SMEs in Bantul Regency - Nugraha Jaka Susanto; Mohamad Irhas Effendi; Sabihaini Sabihaini (International Journal Labs, 2025)
This study aims to analyze the influence of Firm Age and firm size on strategic agility and firm performance, taking into account the moderation of environmental uncertainty to MSMEs in the creative industry sector in Bantul Regency. Data was obtained through the distribution of questionnaires to 104 MSME owners, with 100 valid respondents. Data analysis uses the Smart-PLS method. The results showed that the size of the company had a greater influence on strategic agility and company performance, while environmental uncertainty amplified the impact of strategic agility on company performance. This research provides important insights for MSME managers in optimizing their business strategies in the midst of environmental uncertainty.